COMPETENCES OF FORMING PSYCHOLOGICAL DETERMINANTS OF PRIMARY EDUCATION TEACHERS - Mirkosimova H.M. (European Science Publishing, 2024)
This article reveals the scientific-theoretical foundations of the formation of professional competence of primary school teachers, as well as the role and importance of the factors affecting it. In the following years, in our country, special attention is being paid to the fundamental reform of the education system, further improvement of the personnel training system, and increasing the level of professional training of specialists in this field. In this regard, research aimed at improving the professional qualifications of professors and teachers is of particular importance.
Keywords: psychological competence